o-Nitroaryloxiranyl Aryl Ketones as Versatile Reagents for the Facile Synthesis of 2-Arylquinolines and Quinolin-4-ones - Mamedova, Vera L.; Mamedova, Sevil V.; Korshin, Dmitry E.; Gubaidullin, Aidar T.; Bashirova, Ekaterina S.; Syakaev, Victor V.; Babaeva, Olga B.; Rizvanov, Il'dar Kh.; Gavrilova, Elena L.; Mamedov, Vakhid A. (Synthesis, 2025)
Quinolines and quinolin-4-ones, which are a frequent motif in biologically active molecules, can be prepared from readily available o-nitroaryloxiranyl aryl ketones. The two-stage synthesis of 2-arylquinolines involves the regioselective opening of the oxirane ring with hydrobromic acid or, in some cases, hydrochloric acid to afford 2-halo-3-hydroxy-3-(o-nitroaryl)-1-arylpropan-1-ones and sodium dithionite-mediated intramolecular reductive cyclization. At the same time, o-nitrophenyloxiranyl aryl ketones without other substituents in the 2-nitrophenyl fragment, when exposed to hydrochloric acid in a one-step reaction, form 6-chloro-1,3-dihydroxy-2-arylquinolin-4-ones. The cis-isomer of o-nitrophenyloxiranyl phenyl ketone, when exposed to hydrobromic acid, forms a mixture of 1,3-dihydroxy-2-phenylquinolin-4-one and 6-bromo-1,3-dihydroxy-2-phenylquinolin-4-one, from which a two-component solid solution was isolated in a ratio of the corresponding quinolinones of 0.95:0.05. The cascade processes of quinolin-4-one formation occur without the participation of an external reducing agent, but all functional groups in the molecule, namely the nitro group, oxirane ring, and carbonyl group, are involved in them.
Keywords: o-Nitroaryloxiranyl aryl ketones; Oxirane ring opening; Intramolecular reductive cyclization; 2-Arylquinolines; 2-Arylquinolin-4-ones; Two-component solid solution